2019
DOI: 10.1213/ane.0000000000004166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Right-Lateral Versus Left-Lateral Tilt Position on Compression of the Inferior Vena Cava in Pregnant Women Determined by Magnetic Resonance Imaging

Abstract: BACKGROUND: Despite the existing dogma that women undergoing cesarean delivery under spinal anesthesia should be positioned with a 15° left-lateral tilt, the patients were actually positioned in a right-lateral tilt position in several of the original studies. The superiority of right versus left positioning for optimal inferior vena cava volume is unknown. We used magnetic resonance imaging to compare the effects of right-lateral and left-lateral tilt positions on abdominal aortic and inferior ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 18 publications
4
30
1
3
Order By: Relevance
“…Many studies have demonstrated that velocities or diameters of the compressed IVC and AA could indicate the degree of aortocaval compression by the gravid uterus, and could change dramatically in the supine position during late pregnancy using magnetic resonance imaging (MRI). 10,11,12,13 Lee et al also demonstrated a dramatic change in cardiac output on suprasternal Doppler with patients in the supine position in late pregnancy. 14 However, none of these studies further clari ed the relationship between the degree of aortocaval compression and the incidence of hypotension after spinal anesthesia during cesarean delivery.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have demonstrated that velocities or diameters of the compressed IVC and AA could indicate the degree of aortocaval compression by the gravid uterus, and could change dramatically in the supine position during late pregnancy using magnetic resonance imaging (MRI). 10,11,12,13 Lee et al also demonstrated a dramatic change in cardiac output on suprasternal Doppler with patients in the supine position in late pregnancy. 14 However, none of these studies further clari ed the relationship between the degree of aortocaval compression and the incidence of hypotension after spinal anesthesia during cesarean delivery.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have demonstrated that the velocity or diameter of the compressed IVC could indicate the degree of aortocaval compression by the gravid uterus, and could change dramatically in the supine position during late pregnancy using magnetic resonance imaging (MRI) [12][13][14][15]. Lee et al also demonstrated a significant decrease in cardiac output on suprasternal Doppler, in late pregnancy, with parturients in the supine position, owing to IVC compression by the uterus [16].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that velocity or diameter of the compressed IVC could indicate the degree of aortocaval compression by the gravid uterus, and could change dramatically in the supine position during late pregnancy using magnetic resonance imaging (MRI) [12][13][14][15]. Lee et al also demonstrated a signi cant decrease in cardiac output on suprasternal Doppler with patients in the supine position in late pregnancy due to the IVC compression by the uterus [16].…”
Section: Discussionmentioning
confidence: 99%